2021
DOI: 10.3389/fphys.2021.706545
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Walk Tests in Free-Living Activities Using a Wrist-Worn Device

Abstract: Exercise testing to assess the response to physical rehabilitation or lifestyle interventions is administered in clinics thus at best can be repeated only few times a year. This study explores a novel approach to collecting information on functional performance through walk tests, e.g., a 6-min walk test (6MWT), unintentionally performed in free-living activities. Walk tests are detected in step data provided by a wrist-worn device. Only those events of minute-to-minute variation in walking cadence, which is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Small pauses in walking and changes of posture lasting up to 3 s were ignored ( Del Din et al, 2016 ). However, a minimum average cadence of 60 steps/min was required ( Sokas et al, 2021 ). For the 1-min resting periods, we required 100% heart rate coverage and zero taken steps.…”
Section: Methodsmentioning
confidence: 99%
“…Small pauses in walking and changes of posture lasting up to 3 s were ignored ( Del Din et al, 2016 ). However, a minimum average cadence of 60 steps/min was required ( Sokas et al, 2021 ). For the 1-min resting periods, we required 100% heart rate coverage and zero taken steps.…”
Section: Methodsmentioning
confidence: 99%
“…The previous studies showed good correlation between P6MC cadence and the official P6MC distance; however, the direct transformation from cadence to distance is still challenging [ 38 ]. The sensitivity of this outcome in detecting older individuals with functional capacity has been demonstrated [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The highest continuous activity during 6 min is detected in step data, using a sliding 6 min window with 1 min overlap [ 38 ]. The one with the largest number of steps is chosen as the most representative in order to obtain the highest intensity reached during 6 consecutives minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Unintentional walk testing, which does not modify casual activity habits, may increase the number of pwMS who are less motivated to perform such tests for extended periods. According to a recent study, unintentional walk testing has been shown to be practical and useful for assessing walking capacity in free-living activities ( Sokas et al., 2021 ). Another important limitation is the interpretation of SB during walk test.…”
Section: Discussionmentioning
confidence: 99%